Diffusion flame synthesis of hollow, anatase TiO2 nanoparticles - Karan N.S.; Agrawal A.; Pandey P.K.; Smitha P.; Sharma S.J.; Mishra D.P.; Gajbhiye N.S. (My University, 2025)
Well defined, dense, hollow spheres of anatase titania (TiO2) nanoparticles were produced from TiCl4 (as precursor) by diffusion flame technique. Flow rates of gases (LPG/air/N2 compositions) were found to affect particle size. Titania nanoparticles were observed to decrease from 19 to 8 nm when the air flow rates were increased from 20 to 25 lpm. However, the particle size was found to increase from 15 to 21 nm when the nitrogen flow rate was increased from 0.8 to 2.0 lpm. LPG has been used as fuel. The increase in particle size of anatase TiO2 was due to higher flame height and temperature. The anatase (TiO2) phase was predominant compare to rutile phase in the ratio of 74:26 using air as an oxidant. In the gas phase reaction, the nanoparticles formation occurs due to spontaneous increase of number density of nuclei. The coagulation or aggregation of particles leads to the formation of larger particles due to higher chances of collisions among the particles and sintering at high flame temperature. © 2009 Elsevier B.V. All rights reserved.